Depressive Symptoms and Type 2 Diabetes Mellitus in Rural Appalachia: an 18-Month Follow-Up Study*. (November 2014) - de Groot, Mary; Doyle, Todd; Averyt, Jennifer; Risaliti, Carleen; Shubroo, Jay
Objective: Despite high rates of diabetes and depression in rural areas, limited data exists to document patterns and predictors of depressive symptoms in rural patients with type 2 diabetes (T2DM). The purpose of this study was to assess the rates and predictors of co-morbid depressive symptoms over an 18-month period in a cohort of rural Appalachian adults with T2DM. Methods: N = 100 adult T2DM patients were recruited from family medicine and endocrinology practices located in the rural Appalachian counties of southeastern Ohio and West Virginia. Data were collected using a longitudinal observational survey design. Results: The sample consisted of predominantly White (93%) females (62%) who were married (71%), completed high school or less (48%), and had a mean age of 60 years ( SD 11). Mean BDI score was 14.0 ( SD 12) with 27% scoring in the moderate/severe range for depressive symptoms. A majority of patients (77%) reported depressive symptoms, at both time points, with 88% of these reporting consistent depressive symptoms in the year prior to study follow-up. Patients with depressive symptoms at Time 1 and Time 2 did not differ from other groups in the number of treatment strategies or medications used. Predictors of depressive symptoms in this group were increased diabetes treatment complexity (OR = 2.3), lack of home ownership (OR = 11.4), and decreased satisfaction with antidepressant medications (OR = 2.0; χ 2 = 28.9, p < .0001). Conclusions: Rural T2DM patients reported high rates of repeated depressive symptoms without corresponding rates of depression treatment. These patients may benefit from close monitoring and ongoing adjustment of their treatment for depression and diabetes by primary care providers.